Mean Daily Dosage of Aspirin and the Risk of Incident Alzheimer’s Dementia in Patients with Type 2 Diabetes Mellitus: A Nationwide Retrospective Cohort Study in Taiwan - Cheng-Wei Chang; Jorng-Tzong Horng; Chi-Chang Hsu; Jui-Ming Chen (Journal of Diabetes Research)
Background. Type 2 diabetes mellitus patients are known to have higher risk of developing dementia while aspirin use has been shown to prevent incident dementia. This study was conducted to evaluate the potential benefits of aspirin use on dementia in patients with type 2 diabetes mellitus and identify the appropriate dosage of aspirin that provides the most benefit. Method. A Taiwan nationwide, population-based retrospective 8-year study was employed to analyze the association between the use of aspirin and incidence of dementia including Alzheimer’s disease and non-Alzheimer’s dementia using multivariate Cox-proportional hazards regression model and adjusting for several potential confounders. Results. Regular aspirin use in mean daily dosage of within 40 mg was associated with a decreased risk of developing incident Alzheimer’s dementia in patients with type 2 diabetes mellitus (adjusted HR of 0.51 with 95% CI of 0.27–0.97, p value 0.041). Conclusion. A mean daily dosage of aspirin use within 40 mg might decrease the risk of developing Alzheimer’s disease in patients with type 2 diabetes mellitus.